Adorno's positive dialectic - Sherratt, Yvonne, 1966- (Cambridge University Press, 2002)
This book offers a radically new interpretation of the work of Theodor Adorno. In contrast to the conventional view that Adorno's is in essence a critical philosophy, Yvonne Sherratt traces systematically a utopian thesis that pervades all the major aspects of Adorno's thought.